2022
DOI: 10.1007/s13555-022-00737-7
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Strategies to Inhibit Type 2 Inflammation in Atopic Dermatitis

Abstract: Type 2 immunity evolved to combat helminth infections by orchestrating a combined protective response of innate and adaptive immune cells and promotion of parasitic worm destruction or expulsion, wound repair, and barrier function. Aberrant type 2 immune responses are associated with allergic conditions characterized by chronic tissue inflammation, including atopic dermatitis (AD) and asthma. Signature cytokines of type 2 immunity include interleukin (IL)-4, IL-5, IL-9, IL-13, and IL-31, mainly secreted from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 255 publications
(315 reference statements)
1
44
0
Order By: Relevance
“…A familial study of some cases of PCA has revealed mutations in both genes encoding the subunits of IL-31 receptors (IL31RA and OSMR β)[ 15 ]. It has been demonstrated that IL-4, IL-13, and IL-31 are associated with sensory nerve sensitization and itching in AD patients, leading to scratching that further exacerbates inflammation and barrier dysfunction[ 16 ]. IL-31 is significantly overexpressed in the skin samples of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…A familial study of some cases of PCA has revealed mutations in both genes encoding the subunits of IL-31 receptors (IL31RA and OSMR β)[ 15 ]. It has been demonstrated that IL-4, IL-13, and IL-31 are associated with sensory nerve sensitization and itching in AD patients, leading to scratching that further exacerbates inflammation and barrier dysfunction[ 16 ]. IL-31 is significantly overexpressed in the skin samples of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside these innovative research fields, approaches based more classically on the use of molecularly targeted drugs capable of modifying the inflammatory pathway of AD, acting on several key molecules, such as IL-1α, IL5, IL17, IL25, TLSP, IL31 and IL33, are being researched. Again, the progression in knowledge of the processes underlying the inflammatory cascade has led to the identification of specific and effective molecular targets, whose blockade may improve many features of disease, including pruritus, inflammation, skin barrier disruption and skin colonization [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization lists chronic inflammatory diseases as the most cause of death, [204] considering type 2 inflammation as the main manifestation. For example, asthma [205] (>50%), ulcerative colitis, chronic obstructive pulmonary disease (COPD), and atopic dermatitis [206] are all related to type 2 inflammation. GATA3 is an ideal target to treat type 2 inflammatory disease.…”
Section: Dnazymes Against Chronic Inflammatory Diseasesmentioning
confidence: 99%